Inclusion body hepatitis in a flock of commercial broiler chickens - Bejo, Mohd Hair (Veterinary Association Malaysia, 2005)
Thirty- four-day-old broilers from a flock of chickens in a commercial farm in Perak with history of poor growth and high mortality were submitted for necropsy. On necropsy, mild to moderate enlargement of liver with pale, friable and fatty changes in appearance, and areas of haemorrhage and congestion were observed. The kidney was pale and slightly enlarged. Histologically, numerous eosinophilic and basophilic, round or irregular-shaped intranuclear inclusion bodies were observed in the hepatocytes. The hepatic parenchyma was moderately degenerated and necrotised. Moderate congestion with areas of haemorrhage and moderate to severe infiltration of mononuclear inflammatory cells were also observed in the liver.